"The king of diseases": an essay on the special attention paid to cancer patients and how it came about - Eckart, Wolfgang U. (Ethical challenges in cancer diagnosis and therapy, 2021)
The history of cancer during the twentieth century demonstrates that various factors have contributed to the perception of cancer as the 'Emperor of All Maladies', although this has never been true from an epidemiological perspective. Depending on the geographical area, infectious diseases such as tuberculosis, malaria or cardiovascular disease still head the list of the most common illnesses. Within the group of chronic-degenerative diseases, however, cancer has outdistanced the widespread classic infectious diseases as a result of the epidemiologic transition around 1900, at least in the more developed countries. Under the Nazi dictatorship from 1933 to 1945, the perception of cancer in Germany was particularly promoted for propaganda purposes. In the atomic era, cancer began to attract strong public interest as a worthwhile object of research in radiation therapies using large-scale facilities (electron accelerators, 'electron guns'). A further upsurge of interest in cancer was then registered in the context of the debate about the pathogenic role of environmental factors. The remarkable thing is that this increased perception of cancer has not yet been significantly associated with any overarching success in cancer treatment, but it has been associated with ideologies, hopes and advances in technology.